Arthropod parasites of the red-bellied squirrel Callosciurus erythraeus (Rodentia: Sciuridae) introduced into Argentina - Gozzi, A. C. (2013)
The introduction of an exotic species usually modifies parasite–host dynamics by the import of new parasites or the exotic species' acquiral of local parasites. The loss of parasites may determine the outcome of an invasion if the introduced species is liberated from co-evolved parasites in its range of invasion. In addition, an introduced species may pose sanitary risks to humans and other mammals if it serves as a reservoir of pathogens or carries arthropod vectors. The red-bellied squirrel, Callosciurus erythraeus (Pallas) (Rodentia: Sciuridae), was introduced into Argentina in 1970, since when several foci of invasion have been closely associated with humans. Investigation of the parasitological fauna of C. erythraeus in Argentina will generate new information about novel parasite–host dynamics and may provide new insight into the reasons for the successful invasion of this species. The objective of this study was to describe the arthropod parasites of C. erythraeus in Argentina in comparison with previous studies of parasites of this species in its native habitat and in the ranges of its invasion. Occasional host–parasite associations with local arthropod parasites not previously described for C. erythraeus are reported; these include the mites Androlaelaps fahrenholzi (Ewing) (Mesostigmata: Laelapidae) and Ornithonyssus cf. bacoti (Mesostigmata: Macronyssidae), the flea Polygenis (Polygenis) rimatus Jordan (Siphonaptera: Rhopalopsyllidae) and the botfly Cuterebra Clark (Diptera: Oestridae: Cuterebrinae). Cheyletus sp. mites (Trombidiformes: Cheyletidae) were also found. The low prevalence and mean intensity of ectoparasite species may influence invasion dynamics.